Pendidikan Perilaku Hidup Bersih dan Sehat Masyarakat Kelurahan Pa’bundukang Kecamatan Polombangkeng Selatan Kabupaten Takalar - Nelly Nugrawati; Ekawati, Nur; Wijaya, Ayu (Window of Community Dedication Journal, 2020)
Phbs is a consciously, willing and able to maintain and improve health, prevent the risk of disease and protect ourselves of the illness and actively involved in motion health. One effort from the government in maintaining society not to exposed to the outbreak is by promoting the health of PHBS that is part of promoting the health in the field of environmental health in supporting termination chain for the transmission of covid-19. The community method devotion work with the government at the pabbundukang village and organization adpertisi. A series of events that is providing information about PHBS during pandemic covid19 to the community.